Hubungan antara Intensitas Penggunaan Instagram dengan Body Image pada Emerging Adulthood - Anisa Indriani; Suhana (UNISBA Press, 2023)
Abstract. Body image is an important aspect of human development. The development of technology and the internet today makes social media, one of which is Instagram, related to changes in body image. This study examines the relationship between the intensity of Instagram use and body image in emerging adulthood. The research sample is 140 emerging adulthood aged 18-25 years who live in Bandung obtained through purposive sampling. This research is a quantitative study with a correlational design and the were obtain using the Instagram usage intensity scale and the MBSRQ-AS body image scale. The data were analysed using SPSS 24.0 with the Spearman rho test. The results revealed that there was a relationship between the intensity of Instagram use and body image in emerging adulthood with a correlation coefficient of -.523 and a significance level of .000. The relationship between the intensity of Instagram use and body image has a negative direction, meaning that the higher the intensity of Instagram use, the more negative the individual's body image is and conversely, the lower the intensity of Instagram use, the more positive the individual's body image is. Abstrak. Body image merupakan salah satu aspek penting dalam perkembangan manusia. Berkembangnya teknologi dan internet pada masa kini membuat media sosial, salah satunya instagram dapat berkaitan dengan perubahan pada body image. Penelitian ini akan menguji hubungan antara intensitas penggunaan instagram dengan body image pada emerging adulthood. Sampel dalam penelitian ini adalah 140 emerging adulthood berusia 18-25 tahun di Kota Bandung yang diperoleh menggunakan teknik purposive sampling. Penelitian ini merupakan penelitian kuantitatif dengan desain korelasional dan pengumpulan data menggunakan skala intensitas penggunaan intagram dan skala body image MBSRQ-AS. Analisis data dilakukan menggunakan SPSS 24.0 dengan uji korelasional spearman’s rho. Hasil penelitian menunjukkan bahwa terdapat hubungan antara intensitas penggunaan instagram dengan body image pada emerging adulthood dengan koefisien korelasi sebesar -.523 dan taraf signifikansi sebesar .000. Hubungan antara intensitas penggunaan instagram dengan body image memiliki arah negatif, artinya semakin tinggi intensitas penggunaan instagram maka semakin negatif body image individu dan sebaliknya semakin rendah intensitas penggunaan instagram maka semakin positif body image individu.